Reduction-Triggered Breakable Micelles of Amphiphilic Polyamide Amine-g-Polyethylene Glycol for Methotrexate Delivery. (13th May 2014) - Huang, Yihang; Liu, Jun; Cui, Yani; Li, Huanan; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Abstract : Reduction-triggered breakable polymeric micelles incorporated with MTX were prepared using amphiphilic PAA- g -PEG copolymers having S–S bonds in the backbone. The micelles were spherical with diameters less than 70 nm. The micelles could encapsulate the hydrophobic MTX in the hydrophobic core. The drug loading content and drug loading efficiency of the micelles were highly dependent on the copolymer chemical structure, ranging from 2.9 to 7.5% and 31.9 to 82.5%, respectively. Both the drug loading content and drug loading efficiency increased along with more hydrophobic segments in the copolymers. In normal circumstance, these micelles were capable of keeping stable and hold most of the MTX in the core, stabilizing the incorporated MTX through the π - π stacking with the phenyl groups in the backbone of the copolymers. In reductive environments that mimicked the intracellular compartments, the entire MTX payload could be quickly released due to the reduction-triggered breakage of the micelles. These micelles showed good antiproliferative activity against several cancer cell lines, including KB, 4T-1 and HepG2, especially within the low drug concentration scope.